Thalidomide has a significant effect in patients with thalassemia intermedia. Issue 1 (2nd January 2018) - Li, YunShuan; Ren, Quan; Zhou, Yali; Li, Pingping; Lin, Wanhua; Yin, Xiaolin
ABSTRACT: Objective : To investigate the effect of thalidomide in patients with thalassemia intermedia. Methods: We observed the effect of thalidomide in seven patients with thalassemia intermedia requiring blood transfusion. Four of the patients were transfusion-independent, and three patients were transfusion-dependent. Results: For the four transfusion-independent patients, hemoglobin concentration increased significantly (≥2 g/dl) in three and moderately (1–2 g/dl) in one. After 3 months of treatment, hemoglobin concentration increased 3.2 ± 1.2 g/dl compared to pretreatment. Among the three transfusion-dependent patients, transfusion was terminated after one month of treatment in one patient and decreased >50% in the other two patients, accompanied by an increase in the average hemoglobin concentration. Conclusion: Thalidomide had a significant effect in patients with thalassemia intermedia. Further studies of a larger scale and more rigorous design are warranted.